2012
DOI: 10.1093/infdis/jis361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Strains of RotaTeq Rotavirus Vaccine in Infants With Gastroenteritis Following Routine Vaccination

Abstract: During replication and excretion of RotaTeq vaccine, reassortment of parental strains can occur. Shedding of RotaTeq vaccine strains in 7 of 13 infants was associated with underlying medical conditions that may have altered their immune function. The benefits of vaccination outweigh any small risk of vaccine-associated gastroenteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 38 publications
3
55
1
2
Order By: Relevance
“…The median clinical severity scores for the RVGE cases among vaccine recipients attributed to vaccine virus were less than the clinical severity scores of RVGE cases attributed to wild-type rotavirus, as follows: for RVGE cases attributed to vaccine virus, the median clinical severity score was 4 (range, 1-11) and for RVGE cases attributed to wild-type rotavirus, the median clinical severity score was 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The median clinical severity score of RVGE cases among placebo recipients was 10 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], which is indicative of moderate-to-severe RVGE.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median clinical severity scores for the RVGE cases among vaccine recipients attributed to vaccine virus were less than the clinical severity scores of RVGE cases attributed to wild-type rotavirus, as follows: for RVGE cases attributed to vaccine virus, the median clinical severity score was 4 (range, 1-11) and for RVGE cases attributed to wild-type rotavirus, the median clinical severity score was 6 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The median clinical severity score of RVGE cases among placebo recipients was 10 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], which is indicative of moderate-to-severe RVGE.…”
Section: Resultsmentioning
confidence: 99%
“…The median clinical severity score of RVGE cases among placebo recipients was 10 (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], which is indicative of moderate-to-severe RVGE. The median score reduction between the wild-type RVGE cases among placebo recipients and vaccine-type RVGE among vaccine recipients was 6 (95% confidence interval [CI]: 4, 7); whereas, the median score reduction between the wild-type RVGE cases among placebo recipients and wild-type RVGE among vaccine recipients was 4 (95% CI: -1, 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine-derived reassortant rotaviruses have been detected in association with gastroenteritis in a limited number of patients in a few countries that have implemented rotavirus vaccination programs [23][24][25]. The rotavirus genome is composed of 11 doublestranded RNA gene segments, and two rotavirus strains infecting the same cell can swap genomic segments ( reassortment) to produce progeny with a mosaic genome containing individual genes from each parent.…”
Section: Meeting Reportmentioning
confidence: 99%
“…Rotavirus antigen was detected in the stools of infants for more than a week after their first dose of pentavalent rotavirus vaccine [73]. A recent study in Australia, where the pentavalent RotaTeq is in use since 2007 [74], has shown some circulation of parental as well reassortant vaccine strains in both vaccinated children and subjects sampled in the community in the course of routine surveillance. Also, transmission of vaccine-derived rotavirus (RotaTeq) has been documented in a vaccinee sibling in US, resulting into symptomatic infection that the authors hypothesize may have involved reassortment with a co-infecting wild-type rotavirus [75].…”
Section: Residual Polioviruses In the 2000'smentioning
confidence: 99%